2016
DOI: 10.1177/0300060516657700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urethral catheterization on uroflow during pressure-flow study

Abstract: ObjectiveTo investigate the impact of urethral catheterization on uroflow by comparing urodynamic parameters of free uroflowmetry versus pressure-flow study in adult patients with benign prostatic hyperplasia, female stress incontinence, lumbosacral spinal injury or spina bifida.MethodsEach patient was required to perform pressure-flow study immediately following free uroflowmetry. Maximum flow rate (Qmax), average flow rate (Qave), voided volume (VV), Tmax (time to Qmax) and post-voiding residual urine (PVR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Catheter caliber has been demonstrated to influence Valsalva LPP since measurements with 8Fr catheters resulted in significantly greater LPP than measurements using 3Fr catheters 17 . The effects of urethral catheter presence was also studied in uroflow studies 18 , 19 . In female patients suffering from SUI, flow rate was reduced when using a transurethral catheter, compared to free uroflowmetry 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter caliber has been demonstrated to influence Valsalva LPP since measurements with 8Fr catheters resulted in significantly greater LPP than measurements using 3Fr catheters 17 . The effects of urethral catheter presence was also studied in uroflow studies 18 , 19 . In female patients suffering from SUI, flow rate was reduced when using a transurethral catheter, compared to free uroflowmetry 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of urethral catheter presence was also studied in uroflow studies 18 , 19 . In female patients suffering from SUI, flow rate was reduced when using a transurethral catheter, compared to free uroflowmetry 18 . It has been suggested that this could be due to incomplete sphincter relaxation during voiding with the presence of a transurethral catheter 19 , which may relate to the significantly reduced EUS EMG amplitude if a transurethral catheter was used initially.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the stress of being examined, the presence of urethral catheters has been broadly reported to influence the values of maximum flow rate during pressure‐flow study (PFS) 4 . This observation has been confirmed in female population 5,6 and in a myriad of clinical conditions 7 . The size of the catheter seems to be one of the factors explaining this phenomenon but not the only one 8,9 .…”
Section: Introductionmentioning
confidence: 97%
“…4 This observation has been confirmed in female population 5,6 and in a myriad of clinical conditions. 7 The size of the catheter seems to be one of the factors explaining this phenomenon but not the only one. 8,9 Furthermore, the alterations induced by the catheters have been proposed to be capable of leading to a misdiagnosis of BOO or DU.…”
Section: Introductionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH), as the most common disease in male urological pathology [1], represents a serious public health problem in our contemporary society. Although it is benign, this disease has been shown to have a negative impact on the patient’s health-related quality of life (HRQL), marked by obstructive and irritative lower urinary tract symptoms (LUTS) [2, 3]. Despite continuing development of new minimally invasive surgical methods, transurethral resection of the prostate (TURP) still remains the gold standard surgical treatment for LUTS due to BPH [4, 5], with more than 90% of the patients reporting normal or improved urinary voiding over the 10-year follow-up period.…”
Section: Introductionmentioning
confidence: 99%